Un corpus general de referència de la llengua catalana - Rafel, Joaquim (Caplletra. Revista Internacional de Filologia, 2015)
This work presents the various aspects of the characterization of the Corpus Textual Informatitzat de la Llengua Catalana (Computerized Textual Corpus of the Catalan Language), and analyzes the present State of this project, linked to the preparation of the so-called Diccionari del Català contemporani (Dictionary of Contemporary Catalan) undertaken by the Institut d’Estudis Catalans (Institute of Catalan Studies).